2009
DOI: 10.1261/rna.1442309
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic HPV infection interrupts the expression of tumor-suppressive miR-34a through viral oncoprotein E6

Abstract: MicroRNAs (miRNA) play pivotal roles in controlling cell proliferation and differentiation. Aberrant miRNA expression in human is becoming recognized as a new molecular mechanism of carcinogenesis. However, the causes for alterations in miRNA expression remain largely unknown. Infection with oncogenic human papillomavirus types 16 (HPV16) and 18 (HPV18) can lead to cervical and other ano-genital cancers. Here, we have demonstrated that cervical cancer tissues and cervical cancerderived cell lines containing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
176
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 202 publications
(187 citation statements)
references
References 55 publications
8
176
1
2
Order By: Relevance
“…Several recent studies have shown that E6 and E7 bind to different cell proteins involved in the processes of adhesion, apoptosis, cell cycle, DNA repair, metabolism, signal transduction, transcription and other functions (Horikawa and Barrett, 2003;Whiteside et al, 2008;Howie et al, 2009;McLaughlin-Drubin and Mu¨nger, 2009). In addition, deregulation of the expression of several miRNAs in the host cells associated with HPV infection induced by some of its oncoproteins has been noted by several authors (Martinez et al, 2008;Reshmi and Pillai, 2008;Wang et al, 2008Wang et al, , 2009.…”
Section: Human Papilloma Virusmentioning
confidence: 95%
“…Several recent studies have shown that E6 and E7 bind to different cell proteins involved in the processes of adhesion, apoptosis, cell cycle, DNA repair, metabolism, signal transduction, transcription and other functions (Horikawa and Barrett, 2003;Whiteside et al, 2008;Howie et al, 2009;McLaughlin-Drubin and Mu¨nger, 2009). In addition, deregulation of the expression of several miRNAs in the host cells associated with HPV infection induced by some of its oncoproteins has been noted by several authors (Martinez et al, 2008;Reshmi and Pillai, 2008;Wang et al, 2008Wang et al, , 2009.…”
Section: Human Papilloma Virusmentioning
confidence: 95%
“…Viral oncoprotein E6 or E7 can induce alteration of cellular miRNA expression in different ways during the development and progression of cervical cancer. HPV 16 infection reduced miR-218 expression, resulting in increased expression of LAMB3 (which encodes laminin-5 ␤3), 36 and HPV 16 E6 induced a reduction of miR-34a 14,37 and miR23b, 38 due to the degradation of p53 in cervical cancer cell lines. To determine whether the reduction of miR-375 expression is regulated by HR-HPV oncoproteins, we examined the expression of miR-375 in normal cervical tissues with or without HR-HPV infection.…”
Section: Hr-hpv16 E6/e7 Does Not Directly Regulate Mir-375 Expressionmentioning
confidence: 99%
“…Various miRNA genes are downstream targets of transcription factors such as c-Myc, p53, and E2F and their expression can be modulated by oncogenic HPV E6 and E7 (6). HPV infection in tumor cells can negatively regulate the levels of a specific miRNA (miR-34a) through the inhibition of p53 by the E6 viral protein (7). E6 and E7 HPV viral proteins cause decreased miR-218, a tumor suppressor microRNA (8); miR-125b can directly reduce proliferation of HPV in vitro models.…”
Section: Introductionmentioning
confidence: 99%